Is Prenatal Exercise with Prayer Movement Affecting Anxiety Level and Blood Pressure in Third Trimester? - Meiranny, Arum; Rahmawati, Alfiah; Arisanti, Atika Zahria (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Pregnancy is an important experience in a woman’s life. However, these can cause anxiety. Midwives as a companion must be able to reduce it. In addition, the normality of blood pressure is also influential on the welfare of pregnant and fetuses. One way applied to decrease anxiety and normalize blood pressure is through prenatal exercises. This study aims to determine the prenatal exercise effectiveness with Muslim prayer movement on anxiety and blood pressure in the third trimester in the Independent Practice of Midwives in Karangroto Semarang. This type of research is Quasi-Experiment research with a non-equivalent control group design. Respondents numbered 40 people divided into intervention and control groups. This research took time at the Independent Midwife Practices in October-November 2019. The results showed an effect of the pregnancy exercise movement of prayer on the anxiety and blood pressure of third-trimester pregnant women (p 0.05). This research concludes the effectiveness of prenatal exercise with Muslim prayer movement on anxiety level and blood pressure in the third trimester.